The contextual cogs of “migrant jobs”: A comparative study of the institutional determinants of migrant marginalization in European labor markets - King, Seán (Frontiers in Political Science, 2022)
Migrants play a significant role in European labor markets and are used as sources of “cheap labor”; often being disproportionately represented in low-wage, poor conditions, or otherwise precarious positions. Past research has suggested that the process of migrants being filtered into these low-end occupations is linked to institutional factors in receiving countries such as immigration policy, the welfare state and employment regulation. This paper calculates the extent of migrant marginalization in 17 European countries and uses qualitative comparative analysis (QCA) and regression modeling to understand how institutional factors operate and interact, leading to migrant marginalization. The QCA showed that when a country with a prominent low skills sector and restrictive immigration policy is combined with either strong employment protection legislation or a developed welfare state, migrants will be more strongly marginalized on the labor market. The results of the statistical analysis largely aligned with the idea that restrictive immigrant policy by itself and in combination with other factors can increase marginalization.